Reexamination of crystal growth theory of graphite in iron-carbon alloys. (15th October 2017) - Stefanescu, D.M.; Alonso, G.; Larrañaga, P.; De la Fuente, E.; Suarez, R.
Abstract: Most analysis of graphite morphology in cast iron-carbon alloys is performed on samples cooled to room temperature. This raises the concern that the crystallization of graphite is obscured by subsequent recrystallization and growth in solid state. To bring clarity to this issue, the authors used Field Emission Gun Scanning Electron Microscopy on deep-etched interrupted solidification (quenched) specimens to reveal the morphology of graphite growing in contact with the liquid at the very beginning of solidification. To understand the complexity of graphite crystallization in iron alloys, the analysis included evidence from the crystallization of materials with analogous hexagonal structure, such as of snowflakes and metamorphic graphite, and from the crystallization of diamond cubic structure silicon crystals in aluminum-based alloys. Information from research discussing graphite produced through gas-solid (chemical vapor deposition) and solid-solid (graphite in steel) transformations was also exploited. The large variety of graphite solidification morphologies described in this and earlier papers derives from the complexities of its faceted growth during crystallization, a diffusion-limited crystal growth process, in the presence of anisotropic surface energy and anisotropic attachment kinetics. It was confirmed that the basic building blocks of the graphite aggregates are hexagonal faceted graphite platelets generated through the growth of graphene layers. As solidification advances, the platelets thicken through layer growth through two-dimensional or screw dislocation nucleation. Depending on bulk composition, local supersaturation and undercooling, the platelets aggregate through a variety of mechanisms including tiled-roof and foliated crystals and dendrites, curved-circumferential, cone-helix, helical (macro-spiral), and polyhedral pyramidal (or conical) sectors growth. The final graphite shape of graphite spheroids is affected by the crystallography of the nucleus, as it affects the initial growth of the graphite platelets. Graphical abstract: Image